Mira's diary : home sweet Rome - Moss, Marissa (Moss, Marissa. Mira's diary., 2013)
To rescue her missing mother, thirteen-year-old Mira must travel to sixteenth-century Rome, where she befriends the painter Caravaggio and other artists and scientists under suspicion for being forward thinking individuals.